The Effect of Company Size, Company Age, Profittability and Leverage on Profit Management in Mining Companies Listed on Idx for the 2016-2019 Period - Tina Novianti Sitanggang; Yutni Bernadetta br Tarigan; Kardika Simanjuntak; Andreas Heriyanto Hondro; Widia Andini Amri (Budapest International Research and Critics University, 2022)
This study is designed for the purpose of analyzing and proving the impact of earnings management because of the effect of leverage, profitability; and the age and scale of the companies listed on the Indonesia Stock Exchange for 2016-2019 with the mining business sector. A total of 42 companies were targeted in carrying out the study as the study population, where samples of all of them were selected technically through purposive sampling, which in turn was obtained as many as 64 data samples taken from 4 years of observation from 16 companies that met the criteria for review. At the end of the analysis of the study data, the researcher found that earnings management partially got a significant and negative influence from company size, then a significant and positive effect was obtained from leverage, while no significant effect was found given the profitability and age of the company. And from all of them, obtained a proportion of 22.9% for the coefficient of determination which means the amount of contribution of all variables to earnings management.